Validation of a predictor battery for engineering technicians - Taylor, Jonathan Maclaren (Rhodes University, Faculty of Humanities, Department of Psychology, 1980)
From summary: This study describes a procedure for predicting course success for certain first term engineering technicians. The aim of the study is to reduce the high attrition rate of trainee engineering technicians through the early identification of candidates who are likely to fail their first term of study. This identification is done by testing all applicants to the courses on a battery of psychological tests, and from this information estimating the applicants' first term course results. It is suggested that the student counsellors attached to the various Technikons integrate the suggested procedure into a flexible vocational guidance service for engineering technicians. It should be borne in mind that no validation study can predict future success with a hundred percent accuracy, and that the sample used in this study may be specific to the Witwatersrand Technikon.
Keywords: Occupational aptitude tests; Engineering -- Vocational guidance; Vocational guidance; Prediction (Psychology); Psychological tests